Targeted gene sequencing and whole‐exome sequencing in autopsied fetuses with prenatally diagnosed kidney anomalies. Issue 4 (23rd February 2018) - Rasmussen, M.; Sunde, L.; Nielsen, M.L.; Ramsing, M.; Petersen, A.; Hjortshøj, T.D.; Olsen, T.E.; Tabor, A.; Hertz, J.M.; Johnsen, I.; Sperling, L.; Petersen, O.B.; et al.
Abstract : Identification of fetal kidney anomalies invites questions about underlying causes and recurrence risk in future pregnancies. We therefore investigated the diagnostic yield of next‐generation sequencing in fetuses with bilateral kidney anomalies and the correlation between disrupted genes and fetal phenotypes. Fetuses with bilateral kidney anomalies were screened using an in‐house‐designed kidney‐gene panel. In families where candidate variants were not identified, whole‐exome sequencing was performed. Genes uncovered by this analysis were added to our kidney panel. We identified likely deleterious variants in 11 of 56 (20%) families. The kidney‐gene analysis revealed likely deleterious variants in known kidney developmental genes in 6 fetuses and TMEM67 variants in 2 unrelated fetuses. Kidney histology was similar in the latter 2 fetuses—presenting a distinct prenatal form of nephronophthisis. Exome sequencing identified ROBO1 variants in one family and a GREB1L variant in another family. GREB1L and ROBO1 were added to our kidney‐gene panel and additional variants were identified. Next‐generation sequencing substantially contributes to identifying causes of fetal kidney anomalies. Genetic causes may be supported by histological examination of the kidneys. This is the first time that SLIT‐ROBO signaling is implicated in human bilateral kidney agenesis. Abstract :